Soil fauna promote litter mixture effects on nitrogen release but not carbon or phosphorus during decomposition in a subtropical forest - Pengpeng Dou; Dunmei Lin (Geoderma)
Understanding how litter diversity drives decomposition is critical for linking plant diversity to ecosystem functioning. We conducted a 460-day field decomposition experiment using litter mixtures (1–4 species) placed in both fauna-accessible and excluded litterbags in a subtropical forest. Both additive partitioning and trait-based approaches were used to investigate the effects of litter mixing on mass loss and the release of carbon (C), nitrogen (N), and phosphorus (P). Overall, the litter mixtures exhibited limited non-additive effects on litter mass loss and C release, with significant negative selection effects that offsetting the weak complementarity effects. In contrast, N release showed strong positive net diversity effects in fauna-accessible mixtures, driven by significant complementarity and selection effects. Soil fauna amplified the diversity effect on N release but had no effect on P, which displaying primarily additive dynamics. Functional identity (community-weighted mean of leaf toughness and thickness) predominantly predicted litter mass loss and C release, while functional diversity (Rao’s quadratic entropy of litter N concentration) and identity jointly governed litter N release in the presence of fauna. Our findings demonstrate decoupled mechanisms for C and nutrient cycling, where physical traits constrain mass loss and C release while synergistic litter diversity-soil fauna interactions enhance N mineralization, highlighting context-dependent diversity effects and underscoring the importance of integrating multi-element perspectives and faunal interactions to predict biodiversity-ecosystem functioning relationships in detrital systems.